A paradoxical severe decrease in serum HDL-cholesterol after treatment with a fibrate. Issue 10 (1st October 2000) - Crook, M A; Lynas, J; Wray, R
Abstract : There have been a handful of reports in the literature of a paradoxical decrease in serum high density lipoprotein (HDL)-cholesterol in patients on fibrate drugs. The reason for this decline in cardioprotective HDL-cholesterol is not known and may have potential deleterious effects on the patient. This report describes a decrease in serum HDL-cholesterol in a patient on both simvastatin and bezafibrate. This patient also developed abnormal renal function, probably interstitial nephritis. In addition, the literature of fibrate induced serum HDL-cholesterol decline is reviewed and possible mechanisms for this phenomenon discussed.